1986
DOI: 10.1095/biolreprod35.4.1045
|View full text |Cite
|
Sign up to set email alerts
|

The permeability of the primary decidual zone in the rat uterus: an ultrastructural tracer and freeze-fracture study

Abstract: The rat primary decidual zone (PDZ) is a transitory avascular region of transformed fibroblasts surrounding the implanting embryo. Studies using fluorescein-labeled tracers have shown that the PDZ is selectively permeable to macromolecules, permeability decreasing with increasing molecular weight. In the present study we investigated the morphologic basis of the permeability barrier. Horseradish peroxidase (HRP) or HRP-labeled immunoglobulin G (IgG-HRP) was administered i.v. to rats on Day 7 of pregnancy, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 11 publications
3
32
0
Order By: Relevance
“…This is probably supportive of the formation of incomplete tight junctions in the PDZ Tung et al, 1986). Normal fertility in occludin-deficient mice suggests that it is not crucial during pregnancy (Saitou et al, 2000).…”
Section: Discussionmentioning
confidence: 96%
“…This is probably supportive of the formation of incomplete tight junctions in the PDZ Tung et al, 1986). Normal fertility in occludin-deficient mice suggests that it is not crucial during pregnancy (Saitou et al, 2000).…”
Section: Discussionmentioning
confidence: 96%
“…This removal was evident on the evening of day 5 and raises the possibility that matrix changes may play an inductive role in regulating cellular phenotype (Bissell et al, 1982) and consequently in the process of decidualization (Aplin, 1989). Conversely, transformed cells have been associated with reduced expression of collagen (Kleinman et al, 1981) and thus 1986; Tung et al, 1986) protecting the embryo from the mother's immune response. If such a concept is correct the removal of the fibrillar collagen type I from throughout the decidua should allow closer cellular adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the invasion of trophoblasts into the maternal endometrium, sequential decidual reactions occur and lead to the formation of two distinct zones: the differentiated zone proximal to an implanting embryo termed the primary decidual zone, and the distal peripheral zone consisting of immature mitotic decidual cells, termed the secondary decidual zone [22,23]. In our present study, we have demonstrated that ChM-I is expressed in the primary decidual zone during early pregnancy in mice.…”
Section: Discussionmentioning
confidence: 73%